1992
DOI: 10.1002/hep.1840160331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Zinc on Hepatic Collagen and Prolyl Hydroxylase Activity in Alcoholic Rats

Abstract: The effects of dietary zinc on hepatic collagen and prolyl hydroxylase activity in normal and alcoholic rats has been investigated in four groups of pair-fed male Wistar rats given either liquid ethanol or a control diet for 12 wk. Each group of pair-fed animals received a diet with a different zinc concentration (standard diet, 7.6 mg/L; low-zinc diet, 3.4 mg/L; zinc-supplemented diet, 76 mg/L; and zinc-extrasupplemented, 300 mg/L. There were no significant differences in hepatic collagen concentration and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…2A) and the previous reports on the elevated levels of HPH-2 in response to alcohol exposure, this enzyme does not seem to be the main reason for HIF-1α up-regulation, despite its critical role in the hydroxylation of HIF-1α needed for ubiquitin conjugation and subsequent degradation. For instance, alcohol administration was shown to increase the catalytic activities and levels of HPH, as reported by at least three different laboratories [40-42]. Therefore, it is more likely that the elevated levels of HIF-1α in alcohol-exposed mice (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…2A) and the previous reports on the elevated levels of HPH-2 in response to alcohol exposure, this enzyme does not seem to be the main reason for HIF-1α up-regulation, despite its critical role in the hydroxylation of HIF-1α needed for ubiquitin conjugation and subsequent degradation. For instance, alcohol administration was shown to increase the catalytic activities and levels of HPH, as reported by at least three different laboratories [40-42]. Therefore, it is more likely that the elevated levels of HIF-1α in alcohol-exposed mice (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The mice were then divided into 4 groups, (1) Ctrl, (2) EtOH, (3) Zn and (4) EtOH+Zn, and continually fed for 4 weeks. For zinc supplementation, zinc sulfate was added to the liquid diet at 75 mg elemental zinc/L as described previously 9, 11. At the end of feeding experiment, the mice were anesthetized with Avertin (300 mg/kg) after 4 hrs fasting, and plasma, liver and GAD samples were harvested for assays.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies demonstrated that zinc concentrations in both serum and liver were significantly reduced in patients with alcoholic steatosis, hepatitis and cirrhosis 68. Animal studies showed that dietary zinc supplementation attenuates alcohol-induced liver injury,913 suggesting the importance of zinc in progression of alcoholic liver disease. While the link between zinc and alcoholic steatosis has not been determined, increasing evidence suggest that zinc plays a critical role in regulation of hepatic lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The mice were then divided into four groups: (1) Ctrl, (2) EtOH, (3) Zn, and (4) EtOH+Zn, and continually fed for 4 weeks. For zinc supplementation, zinc sulfate was added to the liquid diet at 75 mg elemental Zn/L as described 9, 11. At the end of the feeding experiment, the mice were anesthetized with Avertin (300 mg/kg body weight) after 4 hours fasting, and plasma, liver, and gonadal adipose depot (GAD) samples were harvested for assays.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies demonstrated that zinc concentrations in both serum and liver were significantly reduced in patients with alcoholic steatosis, hepatitis, and cirrhosis 6–8. Animal studies showed that dietary zinc supplementation attenuates alcohol‐induced liver injury,9–13 suggesting the importance of zinc in progression of alcoholic liver disease. Although the link between zinc and alcoholic steatosis has not been determined, increasing evidence suggest that zinc plays a critical role in regulation of hepatic lipid metabolism.…”
mentioning
confidence: 99%